Microbial Community Response to a Novel Salmon Resource Subsidy - Larson, Courtney E.; Pechal, Jennifer L.; Gerig, Brandon S.; Chaloner, Dominic T.; Lamberti, Gary A.; Benbow, M. Eric (Frontiers in Ecology and Evolution, 2020)
Salmon decomposition is traditionally viewed through the lens of energy and nutrient subsidies, but not as a potential “microbial subsidy.” Microbial communities residing on and within spawning salmon are directly introduced into streams after host death. This incorporation takes the form of microbes sloughing off and integrating into substrate biofilms, or indirectly, by macroinvertebrates facilitating dispersal via consumption. The objective of this study was to determine the effects of salmon carcass-derived microbial communities on stream biofilms and macroinvertebrates during an experimental salmon carcass addition in a naïve stream (i.e., no evolutionary history of salmon). Microbial communities [epilithic biofilms and within macroinvertebrates (internal)] were sampled at treatment and control sites before (September), during (October), and after (November to following August) a salmon carcass subsidy introduction in two successive years (September 2014-August 2016). We found a significant interaction between carcass addition and time on microbial and macroinvertebrate communities. Heptagenia (Heptageniidae: grazer) density was five times higher in the salmon reach compared to the control. In the salmon reach during year one, Stramenopiles (i.e., eukaryotic microbes) decreased in biofilm communities after two weeks of decomposition. The internal microbiome of Stegopterna mutata (Simuliidae: collector-filterer) varied between years but was significantly different between reaches over time during year two of the study, with four times greater abundance of melanogenesis functional pathways (function determined in silico) in the control reach. Although unique microbial taxa, introduced to this naïve stream via salmon carrion, persisted in biofilms on benthic substrate and internal to insects during both years, those taxa represented <2% of the relative abundance in microbial communities. These results highlight the importance of allochthonous carrion resources in the microbial ecology of lotic biofilms and macroinvertebrates. Furthermore, this study contributes to previous research into the complex interkingdom interactions in stream communities in response to a novel allochthonous resource.